Sleep: The forgotten recovery method - Smith, R. A. (Performance Conditioning Cycling)
About the important role of sleep for recovery: - Sleep stages and recovery, - The contribution of sleep and hormones in recovery, - Optimizing sleep patterns, - Pre-competition sleep, - Effects of slee deprivation on athletes, - Getting enough sleep to recover, - Use of catnaps, - Affects of alcohol and use of sleep aids, - Finding help.